1999
DOI: 10.1128/jvi.73.8.6380-6386.1999
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Aid in Protection of the Vaginal Mucosae of Immune Mice against Challenge with Herpes Simplex Virus Type 2

Abstract: Large numbers of polymorphonuclear leukocytes (PMNs) infiltrated the murine vaginal mucosa within 24 h after intravaginal inoculation with an attenuated strain of herpes simplex virus type 2 (HSV-2). The role of these cells in resolution of a primary genital infection and in protection of HSV-immune animals against challenge with a fully virulent HSV-2 strain was investigated. Depletion of greater than 95% of the PMNs at the vaginal mucosal surface prior to intravaginal inoculation with an attenuated HSV-2 str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 41 publications
8
91
0
Order By: Relevance
“…Significant levels of Th1 responses were induced following immunization, as indicated by the production of high levels of IFN-g compared with IL-4 levels that remained unchanged up to 8 weeks postimmunization. IFN-g has been shown to be involved in the clearance of HSV-2 from the vaginal mucosa of nonimmune mice and in resistance to reinfection in immune mice (Smith, 1994;Milligan & Bernstein, 1997;Milligan et al, 1998). The Groups of mice were immunized as described in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Significant levels of Th1 responses were induced following immunization, as indicated by the production of high levels of IFN-g compared with IL-4 levels that remained unchanged up to 8 weeks postimmunization. IFN-g has been shown to be involved in the clearance of HSV-2 from the vaginal mucosa of nonimmune mice and in resistance to reinfection in immune mice (Smith, 1994;Milligan & Bernstein, 1997;Milligan et al, 1998). The Groups of mice were immunized as described in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this interpretation, IFN-c secretion in immune/ challenged mice was abolished by in vivo depletion of T cells with mAb. 7 The IFN-c that was secreted in immune/challenged BALB/c mice up-regulated the expression both of MHC class II antigens in the vaginal epithelium 10 and VCAM-1 in vascular endothelial cells, 17 and it recruited large numbers of T and B lymphocytes to the vaginal mucosa. 10 These responses were blocked by pretreatment in vivo with mAb to IFN-c.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that protective immunity in these mice depended mainly on CD4 + lymphocytes. Similarly, Milligan et al 7 concluded that T-cell immunity is required for protection of the vaginal mucosa, even in the presence of high titres of speci®c HSV-2 antibody, and Sin et al 15 reported that a T helper 1 (Th1)-type immune response provided protective immunity against vaginal herpes infection whereas a T helper 2 (Th2)-type immune response worsened the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In response to the initial infection, natural killer (NK) cells, NKT cells, and neutrophils are recruited to the area along with the production of a number of soluble factors including interleukin-12 (IL-12), IL-15 and IL-18, all of which are found to contribute to the innate defence against HSV-2. [3][4][5][6] In addition, recognition by toll-like receptor 9 of HSV-2 DNA leads to the production by plasmacytoid dendritic cells of type I interferons (IFNs), 7 a family of antiviral cytokines that have been found to suppress genital HSV-2 replication in vivo. 8 Even though a robust innate immune response ensues, HSV-2 can successfully infect and replicate in the host.…”
Section: Introductionmentioning
confidence: 99%